2018
DOI: 10.1038/s41598-017-18616-z
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Seventeen Inflammatory Mediators are Associated with Patient Outcomes in Severe Fever with Thrombocytopenia Syndrome

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) as an emerging infection disease results in high morbidity and mortality in China. In this study, the circulating levels of 36 inflammatory mediators in 33 SFTS patients on days 3-7, 8-12 and 13-20 post-illness were measured by a multiplex Luminex ® system dynamically. Among the patients, 15 severe patients recovered, 11 severe patients died within three weeks. We found IL-1RA, IL-6, IL-15, IL-10, TNF-α, IFN-γ, G-CSF, eotaxin, IL-8, IP-10, MCP-1, MIP-1α, MIP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 29 publications
6
43
0
Order By: Relevance
“…Our work highlights the previously underappreciated function of platelets in modulating immunity, adding to the growing evidence that platelet parameters, such as counts and activation, are causes of variation in the concentrations of circulating cytokines (Hu et al, 2018; Schirmer et al, 2018; Tunjungputri et al, 2018). Although best known for their role in thrombosis, platelets secrete a host of proteins (Coppinger, 2004; Maynard et al, 2007), and can modulate the function of leukocytes by forming heterotypic aggregates (Kral et al, 2016).…”
Section: Discussionmentioning
confidence: 63%
“…Our work highlights the previously underappreciated function of platelets in modulating immunity, adding to the growing evidence that platelet parameters, such as counts and activation, are causes of variation in the concentrations of circulating cytokines (Hu et al, 2018; Schirmer et al, 2018; Tunjungputri et al, 2018). Although best known for their role in thrombosis, platelets secrete a host of proteins (Coppinger, 2004; Maynard et al, 2007), and can modulate the function of leukocytes by forming heterotypic aggregates (Kral et al, 2016).…”
Section: Discussionmentioning
confidence: 63%
“…We and others have previously shown that by using whole blood this assay can be simplified substantially ( 2 , 42 ). Other methods assessing the MTB-specific cytokine secretion upon whole blood stimulations may also allow specific diagnoses of active TB ( 43 ), whereas monitoring the TB treatment response using the latter approach so far appears less promising ( 44 ). The measurement of soluble biomarkers in the blood without prior stimulation also may hold valuable information on TB disease and treatment status ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In uencing factors of poor prognosis were mainly associated with viral load, cytokine function and T cell number [17]. Hu reported that the imbalance of in ammatory response in SFTSV infection was related to the mortality rate [18]. Some studies have shown that age, GOT levels, central nervous system involvement and bleeding tendency could affect the prognosis of the patients with SFTSV infection [19,20].…”
Section: Discussionmentioning
confidence: 99%